The Presence of Growth Mindset Online Intervention in Education: Bibliometric Analysis - Selfiyani Lestari; Farhan Zakariyya; Abu Ammar Tajuddin Al Azizy; Ghinaya Ummul Mukminin Hidayat; Muhammad Ariez Musthofa; Engkos Kosasih (Yayasan Keluarga Guru Mandiri, 2025)
The use of online media in the realm of education is a trend nowadays. Not only is it used to support the learning process, it also supports students' psychological conditions. One of them is creating a growth mindset. The aim of the research is to describe the development of online interventions for growth mindsets used in the educational domain. Bibliometric analysis was used in this study. Data pertaining to articles published on Google Scholar relevant to this research topic were gathered utilizing the Publish or Perish application. Furthermore, the data was analysed using the VOSviewer application. The results of the analysis revealed that the use of online-based interventions was developed and used to improve students' growth mindset in the current educational domain. Various online-based intervention designs have been developed and scientifically researched for their impact on growth mindset in the education domain. This research can serve as a basis for creating growth mindset-based media interventions for students in the context of education.